2018
DOI: 10.6001/actamedica.v24i4.3613
|View full text |Cite
|
Sign up to set email alerts
|

The role of MMP-1 and FGFR4-R388 gene polymorphisms in pituitary adenoma

Abstract: Background.The pathogenesis of pituitary adenoma (PA) is complex and poorly understood. It is thought that PA has a multifactorial aetiology; genetic factors also have an impact on PA development. Since MMP1 and FGFR4 genes play an important role in tumour growth, differentiation and progression, we decided to determine if the frequency of the genotypes of MMP-1 and FGFR4-R388 polymorphisms influence the development of PA.Materials and methods.The study enrolled n = 100 patients with PA and n = 200 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…PA account for 10%‐15% of all intracranial tumors . Although most PA are histologically benign tumors, their location in the brain makes them very serious .…”
Section: Discussionmentioning
confidence: 99%
“…PA account for 10%‐15% of all intracranial tumors . Although most PA are histologically benign tumors, their location in the brain makes them very serious .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PAs exhibiting high MMP activity can be associated with aggressive tumor phenotype. Zlatkute et al (2017) discussed the role of MMP-1 polymorphisms on the development of PAs by analyzing genetic profiles of 100 patients with PA and comparing them with healthy controls [20]. They found that the polymorphism in the MMP-1 gene 1G/1G was more frequent in the invasive group of PAs and in the more active tumors than in control PAs (p = 0.044), suggesting that this polymorphism may play a role in PA development [20].…”
Section: Snps Found In Pas In General (Functional and Nonfunctional)mentioning
confidence: 99%
“…Zlatkute et al (2017) discussed the role of MMP-1 polymorphisms on the development of PAs by analyzing genetic profiles of 100 patients with PA and comparing them with healthy controls [20]. They found that the polymorphism in the MMP-1 gene 1G/1G was more frequent in the invasive group of PAs and in the more active tumors than in control PAs (p = 0.044), suggesting that this polymorphism may play a role in PA development [20]. This was in contrast to a previous paper by Atlas et al (2010), in which they found that MMP-1 2G/2G alleles were more common in the invasive PAs than 1G/1G variants, but that allelic pattern was not statistically significant compared with control [21].…”
Section: Snps Found In Pas In General (Functional and Nonfunctional)mentioning
confidence: 99%